Home-based enteral nutrition self-management challenges in young and middle-aged patients with Crohn’s disease: a qualitative study - Jing Wang; Meng Yang; Zhehao Zhang (BMJ Open)
Objectives To explore the challenges faced by young and middle-aged patients with Crohn’s disease (CD) in managing home enteral nutrition (HEN) and to identify strategies to improve their self-management and treatment adherence. Design A qualitative phenomenological study. Setting The study was conducted at a comprehensive tertiary hospital in Jiangsu, China, with a focus on patients undergoing long-term HEN treatment for CD. Participants 14 participants, aged 18–60 years, diagnosed with CD, and receiving HEN. Inclusion criteria required participants to be capable of clear self-expression and to provide voluntary consent. Exclusion criteria included cognitive impairment, mental illness or other major health conditions unrelated to CD. Interventions Data were collected through semistructured interviews, exploring participants’ self-management challenges with HEN. Outcomes 14 valid interviews were included for analysis. Two main themes were identified: subjective challenges, including psychological burden, self-management confidence and disease perception bias, and objective challenges, including social restrictions, economic burden and insufficient support systems. Conclusions Young and middle-aged patients with CD face significant subjective and objective challenges in managing HEN, which impact their physical and psychological well-being. Targeted interventions are needed to address these difficulties and improve self-management support.